Isolation, Identification and Essential Oil Control of Pathogenic Fungi in Postharvest Blueberry - WAN Chunxiu, ZHANG Chuxuan, XIE Zihan, KANG Chenrui, TAO Nengguo, TAN Xiaoli (Shipin Kexue, 2025)
To reduce postharvest losses caused by pathogen infection in blueberry fruit, this study aimed to isolate and identify the pathogens responsible for blueberry fruit rot and to develop environmentally friendly and safe disease control measures. Through tissue isolation, four pathogenic fungi were obtained from naturally infected blueberry fruit, which were identified as Penicillium crustosum, Aspergillus tubingensis, Alternaria alternata, and Fusarium verticillioides based on morphological and molecular analyses. The pathogenicity of these pathogens was ranked as follows: P. crustosum > A. tubingensis > A. alternata > F. verticillioides. All pathogens except F. verticillioides, having low pathogenicity, were selected to analyze their growth and development conditions. The optimal growth temperature for the three fungi was between 25 and 28 ℃. The growth curves showed that the logarithmic growth phase lasted less than 66 h, and spore germination occurred within 12 h. Furthermore, the in vitro effects of 25 natural plant essential oils (EOs) on the pathogens were explored. It was found that most EOs had a potent inhibitory effect on the growth of P. crustosum and A. tubingensis. Among them, jasmine, Ocimum gratissimum L., Litsea cubeba, and Rhodiola rosea essential oils at 2 μL/mL could completely inhibit the growth of all four fungi in vitro, and 2 μL/mL of Dipsacales essential oil could inhibit the growth of P. crustosum, A. tubingensis and A. alternata, with an inhibition rate of 97% for F. verticillioides. In vivo experiments showed that fumigation with L. cubeba or jasmine essential oil significantly reduced the incidence of diseases in blueberry fruit inoculated with P. crustosum, with the former showing a more pronounced effect. Thus, L. cubeba essential oil is expected to be a green alternative measure for controlling blueberry fruit diseases during storage.